# cos(3x)-cos(2x)=0

## Simple and best practice solution for cos(3x)-cos(2x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for cos(3x)-cos(2x)=0 equation:

Simplifying
cos(3x) + -1cos(2x) = 0
Remove parenthesis around (3x)
cos * 3x + -1cos(2x) = 0
Reorder the terms for easier multiplication:
3cos * x + -1cos(2x) = 0
Multiply cos * x
3cosx + -1cos(2x) = 0
Remove parenthesis around (2x)
3cosx + -1cos * 2x = 0
Reorder the terms for easier multiplication:
3cosx + -1 * 2cos * x = 0
Multiply -1 * 2
3cosx + -2cos * x = 0
Multiply cos * x
3cosx + -2cosx = 0
Combine like terms: 3cosx + -2cosx = 1cosx
1cosx = 0
Solving
1cosx = 0
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Divide each side by '1'.
cosx = 0
Simplifying
cosx = 0
The solution to this equation could not be determined.`